Static Analysis of Tubular Space Frame Chassis of an Electric Racing Car Made of ASTM A106 Grade B - Encu Saefudin; Nuha Desi Anggraeni; Marsono Marsono; Syauqi Azhari (Department of Mechanical Engineering, Universitas Andalas, 2023)
The chassis is a vital component in electric vehicles, which can keep the car rigid and robust to support the load on it. In this research, the chassis is designed for electric vehicles with sufficient strength and rigidity, as well as light in weight and safety according to KMLI regulations, to be used in student racing competitions. The design process is begun with chassis space frame determination and weight and position definition of all components to be installed on the chassis. Then calculate the centre of gravity and the reaction force at the mounting supports on each wheel. The chassis design has a length of 2300mm, a width of 1100mm and a height of 1100 mm. This chassis is made using ASTM A106 Grade B steel pipe with a diameter of 1 inch, and the total weight is 76.5 kg. The analysis was carried out statically using Solidwork. The static study showed maximum stress of 22.06 MPa, a maximum deflection of 0.346 mm, and a minimum safety factor of 10.9. All the parameters show promising results, strength, stiffness, and safety in compliance with KMLI regulations